A framework of outsourcing relationship marketing: a focus on the Malaysian hotel industry. (3rd February 2010) - Abdul-Rahman, Maria; Kamarulzaman, Yusniza
This study contributes to the body of knowledge by examining the antecedents of outsourcing relationship quality among the management of Malaysian hotels and their service providers. This study is important considering that the quality of relationship between client firms and their service providers adds positive image to the entire system and is crucial for the delivery of the benefits of outsourcing arrangement. Identifying the determinants of the outsourcing relationship quality is important due to its effect on outsourcing ventures. A firm should have a strong relationship with its service provider since a high relationship quality has been proven to provide positive impact on outsourcing. This study examines the effect of relational norms on the quality of relationship among hotel managements and their service providers. Hotel industry has been the focus of this study due to its significant contribution to the service sector as the largest contributor of the Malaysian economy.